Sistem Pakar Troubleshooting Kerusakan Hardware Komputer Berbasis Web Dengan Metode Forward Chaining Pada Laboratorium STMIK Kharisma Makassar - Faisal T Supu; Sofyan S. Thayf; Marlina (JTRISTE, 2026)
This research aims to develop a web-based expert system designed to assist in troubleshooting computer hardware issues at the STMIK Kharisma Makassar Laboratory. The system employs a forward chaining method to diagnose problems based on symptoms reported by users. The research methodology utilized is R&D with a descriptive and quantitative approach. Test results indicate that this system can deliver accurate diagnoses and relevant solutions, thereby enhancing efficiency in addressing hardware damage issues.